Contribution to the experimental study of trypsin intracanalicular - Carrillo Maurtua, Luis (1956)
The claim that trypsin is inactive within the intrapancreatic channels for many years has been recorded in the classical treatises of physiology ago. However, contrary to some experimenters have indisputably classic dogma extracted pancreatic trypsin active channels. This extremely interesting, not only for its absolute value but especially by their projections to the pathophysiology of pancreatitis should be controlled in multiple and rigorous experiments. We have personally made a short experimental study in the dog. Are the results of this experiment we committed in this preliminary work.